Late Glacial–Holocene transition climate inferred from the palynological records in the western and eastern Amazon Basin - Bowen Wang; Kamaleddin Alizadeh; Jackson Martins Rodrigues; Hermann Behling (Review of Palaeobotany and Palynology, 2026)

Late Holocene vegetation and environmental dynamics in Tripa Peat Swamp Forest - Leuser Ecosystem, Aceh, Indonesia - Arif Habibal Umam; Hermann Behling (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Modern pollen–vegetation relationships in north-central Oman and their implications for interpreting fossil pollen records from extremely arid environments - Julia Unkelbach; Lucas Proctor; Hermann Behling (Palynology, 2026)

Pollen composition in the corbicula reflects the foraging activity of sympatric honey bees and stingless bees in Indonesia - Tiara Sayusti; Rika Raffiudin; Nina Ratna Djuita; Dyah Perwitasari-Farajallah; Irmanida Batubara; Windra Priawandiputra; Rahmadi Sitompul; Svea Lina Jahnk; Hermann Behling (Palynology, 2026)

Corrigendum to “Late Holocene vegetation and environmental dynamics in Tripa Peat Swamp Forest - Leuser Ecosystem, Aceh, Indonesia [Palaeogeogr., Palaeoclimatol., Palaeoecol. 699 (2026) 113987] - Arif Habibal Umam; Hermann Behling (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Environmental change and imperial land use in central Mongolia: a multiproxy lake record from the vicinity of Karakorum over the last 1260 years - Chéïma Barhoumi; Hendrik Rohland; Christina Franken; Choimaa Dulamsuren; Davaadorj Saindovdon; Hermann Behling (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Late Holocene vegetation dynamics, fire regimes, and human impact in Southern Brazil: A multi-proxy palaeoecological record from the Matematico Lake - Antonia Lena Reinhardt; Philip Riris; Barnabas Harris; Deepak Kumar Jha; Gisele Leite de Lima Primam; Soraia Girardi Bauermann; Kasun Gayantha; Rachel Rudd; Patrick Roberts; Hermann Behling (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Reconstruction of vegetation, climate, fire and human activity at an Iron Age oasis site in Lizq, northern Central Oman, beginning in 400 cal yr BCE - Julia Unkelbach; Hermann Behling; Conrad Schmidt (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Meridional shifts of Brazil-Malvinas Confluence since the Last Glacial Maximum - Fang Gu; Karin A.F. Zonneveld; Hermann Behling (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Steppe development and mammalian adaptation in the middle Miocene, North Junggar Basin, Central Asia - Jian Wang; Xinying Zhou; Shiqi Wang; Jie Ye; Junchi Liu; Wenyu Wu; Yan Wu; Keliang Zhao; Yan Zheng; Hermann Behling; Xiaoqiang Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The last millennium vegetation and environmental history of the Hyrcanian highland region, a pollen record from Shekardasht mire, northern Iran - Faezeh Nourmohammad; Elias Ramezani; Hermann Behling (Review of Palaeobotany and Palynology, 2024)

Tracing the dynamics of Late Holocene Tropical Peatland: A case study from the Bram Itam Peatland Protection Area, Coastal Sumatra, Indonesia - Chung Hoai Nguyen; Svea Lina Jahnk; Asmadi Saad; Supiandi Sabiham; Hermann Behling (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Holocene vegetation, fire, climate dynamics and human impact in the upper Orkhon Valley of the Khangai Mountains, Mongolia - Chéïma Barhoumi; Marcel Bliedtner; Roland Zech; Hermann Behling (Quaternary Science Reviews, 2024)

Late Quaternary Araucaria forest and Campos (grasslands) vegetation dynamics inferred from a high-resolution pollen record from Lagoa Dourada in southern Brazil - Daniela Piraquive-Bermúdez; Hermann Behling; Bernd Zolitschka; Thomas Giesecke (Quaternary Science Reviews, 2024)

Human impact on vegetation at Lago di Vedana (Dolomites, Northern Italy) during the last seven centuries - Irene Sophie Polgar; Bernd Zolitschka; Hermann Behling (Anthropocene, 2023)

Holocene environmental changes inferred from an oxbow lake in a Mauritia palm swamp (aguajal) in the Madre de Dios region, southeastern Peru - Bowen Wang; Viviana Horna; Matthias Heckmann; K. Anggi Hapsari; Reiner Zimmermann; Hermann Behling (Review of Palaeobotany and Palynology, 2023)

C4 expansion of Central Asia in the middle Miocene linked to the strengthening Indian monsoon - Jian Wang; Xinying Zhou; Shiqi Wang; Hai Xu; Hermann Behling; Jie Ye; Yan Zheng; Junchi Liu; Yan Wu; Keliang Zhao; Ran Zhang; Xiaoqiang Li (Global and Planetary Change, 2023)

Late Holocene paleoenvironmental changes inferred from multi-proxy studies of the Kholasht-Kouh Lake sediments in the Gilan mountains, northern Iran - Leila Homami Totmaj; Kammaledin Alizadeh; Hermann Behling (Journal of Paleolimnology, 2022)
Past vegetation and environmental changes and the role of climate as well as human activities are of major interest. The Hyrcanian region with a high number of endemic species has a poorly known paleoenvironmental history, especially the western region of northern Iran. This study aims to investigate a radiocarbon-dated sediment core of the Kholasht-Kouh Lake (KHL) for the recorded between ca. 510 and 1180 cal yr BP. KHL is located at 2000 m elevation and surrounded with steppe vegetation above the present-day forest line. Multi-proxy analyses including pollen, non-pollen palynomorphs, charcoal, loss on ignition, and X-ray fluorescence were applied to reconstruct past environmental dynamics. The results indicate the dominance of herbaceous vegetation (mainly Poaceae, Artemisia , and Amaranthaceae) around the lake during the whole record, except for the period between 1010 and 740 cal yr BP. During this period of the Medieval Climatic Anomaly (1000–700 cal yr BP) mixed forest increased, consisting mainly of Quercus , Fagus , Carpinus , and Juniperus . The K, Ti and Si elements (as indicators for increased in detrital inputs) suggest relatively humid condition between 1180 and 1010 cal yr BP. Furthermore, higher lake levels may indicate from low values of the Mn/Ti, Ca/Ti and Sr/Ti ratios. After 1010 until 740 cal yr BP the highest value of the Si/Fe ratio, suggested warmest period of the record. While the lowest value of the Si/Fe ratio, in line with the reduction of other elements and ratios, between 740 till 510 cal yr BP represented cold and dry period. Humans were present around the study area at least since beginning of the record, but did not played an important role impacting the vegetation.

In memoriam Prof. em. Dr. Hans-Jürgen Beug, 18th January 1932 to 5th March 2022 - Hermann Behling; Lydie M. Dupont; Susanne Jahns; Frank Schlütz; Joerg Christiansen; Felix Bittmann (Vegetation History and Archaeobotany, 2022)

Late Holocene Vegetation and Environmental Changes of Coastal Lowlands in Northern Iran: Possible Role of Climate, Human Impact and Caspian Sea Level Fluctuations - Fang Gu; Kamaleddin Alizadeh; Hermann Behling (Wetlands, 2022)
Coastal forests and wetlands play an important role in supporting biodiversity, protecting the hinterlands and shorelines from erosion and also contributing to carbon sequestration and freshwater storage. To reconstruct late Holocene vegetation and environmental dynamics in the coastal lowlands of northern Iran and to detect the possible role of climate, human and Caspian Sea level fluctuation on coastal ecosystems, multi-proxy analysis was applied on the sediment cores from the inland Eynak (EYK) lagoon and near coast Bibi Heybat (BBH) alder swamp. Results shows that in the last 170 years, strong reduction of alder forest occurred around Eynak lagoon, while an expansion occurred in the coastal area in the last 100 years. This indicates that human impact shifted from the near coast to elevated inland, which might be due to the raised water level from the Caspian Sea and the coastal area of BBH region was flooded by brackish water from the Caspian Sea, and was not so suitable for agriculture anymore. This study indicate that alder swamp extent is different between coastal and inland sites, suggesting that further studies of multiple records across the region are needed. Moreover, this study helps to distangle human impacts from wetland processes and thus will be an important contribution to effective climate mitigation and conservation strategies. This multi-proxy study presents important palynological records, which helps to understand past and future impacts of various drivers, such as climate, human impact and sea level changes on wetland ecosystems both regionally and globally.

Sea level rise and climate change acting as interactive stressors on development and dynamics of tropical peatlands in coastal Sumatra and South Borneo since the Last Glacial Maximum - K. Anggi Hapsari; Tim Jennerjahn; Septriono Hari Nugroho; Eko Yulianto; Hermann Behling (Global Change Biology, 2022)
Southeast Asian peatlands, along with their various important ecosystem services, are mainly distributed in the coastal areas of Sumatra and Borneo. These ecosystems are threatened by coastal development, global warming and sea level rise (SLR). Despite receiving growing attention for their biodiversity and as massive carbon stores, there is still a lack of knowledge on how they initiated and evolved over time, and how they responded to past environmental change, that is, precipitation, sea level and early anthropogenic activities. To improve our understanding thereof, we conducted multi‐proxy paleoecological studies in the Kampar Peninsula and Katingan peatlands in the coastal area of Riau and Central Kalimantan, Indonesia. The results indicate that the initiation timing and environment of both peatlands are very distinct, suggesting that peat could form under various vegetation as soon as there is sufficient moisture to limit organic matter decomposition. The past dynamics of both peatlands were mainly attributable to natural drivers, while anthropogenic activities were hardly relevant. Changes in precipitation and sea level led to shifts in peat swamp forest vegetation, peat accumulation rates and fire regimes at both sites. We infer that the simultaneous occurrence of El Niño‐Southern Oscillation (ENSO) events and SLR resulted in synergistic effects which led to the occurrence of severe fires in a pristine coastal peatland ecosystem; however, it did not interrupt peat accretion. In the future, SLR, combined with the projected increase in frequency and intensity of ENSO, can potentially amplify the negative effects of anthropogenic peatland fires. This prospectively stimulates massive carbon release, thus could, in turn, contribute to worsening the global climate crisis especially once an as yet unknown threshold is crossed and peat accretion is halted, that is, peatlands lose their carbon sink function. Given the current rapid SLR, coastal peatland managements should start develop fire risk reduction or mitigation strategies.

Created by the Monte Peron rock avalanche: Lago di Vedana (Dolomites, Italy) and its sediment record of landscape evolution after a mass wasting event - Bernd Zolitschka; Irene Sophie Polgar; Hermann Behling (Landslides, 2022)
The timing of the Monte Peron Landslide is revised to 2890 cal. BP based on a radiocarbon-dated sediment stratigraphy of Lago di Vedana. This age fosters the importance of hydroclimatic triggers in the light of accelerating global warming with a predicted increase of precipitation enhancing the regional predisposition to large landslides. Moreover, a layer enriched in allochthonous organic and minerogenic detritus dating to the same wet period is interpreted as response to a younger and yet unidentified mass wasting event in the catchment of Lago di Vedana. Rock debris of the Monte Peron Landslide impounded the Cordevole River valley and created a landslide-dammed lake. Around AD 1150, eutrophication of this lacustrine ecosystem started with intensified human occupation – a process that ended 150 years later, when the river was diverted back into its original bed. Most likely, this occurred due to artificial opening of the river dam. In consequence, Lago di Vedana was isolated from an open and minerogenic to an endorheic and carbonaceous lacustrine system. After a monastery was established nearby in AD 1457, a second eutrophication process was initiated due to intensified land use linked with deforestation. Only in the eighteenth and nineteenth centuries, deposition of organic matter decreased coinciding with climatic (Little Ice Age) and cultural changes. Conversational measures are the likely reasons for a trend towards less eutrophic conditions since AD 1950.

Four millennia of vegetation and environmental history above the Hyrcanian forest, northern Iran - Leila Homami Totmaj; Elias Ramezani; Kammaledin Alizadeh; Hermann Behling (Vegetation History and Archaeobotany, 2021)
Past vegetation, fire, and climate dynamics, as well as human impact, have been reconstructed for the first time in the highlands of the Gilan province in the Alborz mountains (above the Hyrcanian forest) for the last 4,300 cal yrs bp . Multi-proxy analysis, including pollen, spores, non-pollen palynomorphs, charcoal, and geochemical analysis, has been applied to investigate the environmental changes at 2,280 m a.s.l., above the Hyrcanian forest. Dominant steppe vegetation occurred in the study area throughout the recorded period. The formation of the studied mire deposits, as well as vegetation composition, suggest a change to wetter climatic conditions after 4,300 until 1,700 cal yrs bp . Fires were frequent, which may imply long-lasting anthropogenic activities in the area. Less vegetation cover with a marked decrease of the Moisture Index (MI) suggests drier conditions between 1,700 and 1,000 cal yrs bp . A high proportion of Cichorioideae and Amaranthaceae, as well as the reduction of trees, in particular Fagus and Quercus , at lower elevations, indicate human activities such as intense livestock grazing and deforestation. Soil erosion as the result of less vegetation due to dry conditions and/or human activities can be reconstructed from a marked increase of Glomus spores and high values of K and Ti. Since 1,000 cal yrs bp , the increasing MI, as well as the rise of Poaceae and Cyperaceae together with forest recovery, suggest a change to wetter conditions. The occurrence of still frequent Cichorioideae and Plantago lanceolata along with Sordaria reflect continued intense grazing of livestock by humans.

Correction to: Intensification of agriculture in southwestern Germany between the Bronze Age and Medieval period, based on archaeobotanical data from Baden-Württemberg - Gegeensuvd Tserendorj; Elena Marinova; Jutta Lechterbeck; Hermann Behling; Lucia Wick; Elske Fischer; Marion Sillmann; Tanja Märkle; Manfred Rösch (Vegetation History and Archaeobotany, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00334-021-00835-0

Long-term persistence of steppe vegetation in the highlands of Arasbaran protected area, northwestern Iran, as inferred from a pollen record - Elias Ramezani; Taravat Talebi; Kamaledin Alizadeh; Anoushirvan Shirvany; Behnam Hamzeh’ee; Hermann Behling (Palynology, 2021)

Intensification of agriculture in southwestern Germany between the Bronze Age and Medieval period, based on archaeobotanical data from Baden-Württemberg - Gegeensuvd Tserendorj; Elena Marinova; Jutta Lechterbeck; Hermann Behling; Lucia Wick; Elske Fischer; Marion Sillmann; Tanja Märkle; Manfred Rösch (Vegetation History and Archaeobotany, 2021)
A system of farming with an alternation of land use between being cultivated or left fallow as grassland ( Feldgraswirtschaft ) developed in southwestern Germany since the Bronze Age. It involved fallow periods, where the arable land is left without crops in order to let it recover its fertility for several years while becoming grassland. This led to regeneration of the topsoil humus, which could later be mobilized by cultivation. With later farming systems, the supply of nutrients needed for crops could also be provided by manuring, which allowed shorter fallow periods but required the production of manure. Such cultivation systems with short or even without fallow phases and with intensive manuring are known from the medieval period as one, two or three field systems of agriculture and their development was an important step towards the intensification of farming. The current study considers on-site plant macrofossil data from archaeological sites as well as the off-site pollen data from cores in Baden-Württemberg in order to recognize the main changes towards agricultural intensification through time from the Bronze Age up to medieval times. The various landscape types included in the study area also reveal their different agricultural histories of intensification. In lowlands with good soils, the intensification can be recognized earlier and more strongly than in uplands or other marginal areas. The main shift towards intensification took place in the Roman period, which is also confirmed by written sources of the time that mention manuring as well as a kind of two field system and alternation between grassland and arable land.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Intertwined effects of climate and land use change on environmental dynamics and carbon accumulation in a mangrove‐fringed coastal lagoon in Java, Indonesia - K. Anggi Hapsari; Tim C. Jennerjahn; Martin C. Lukas; Volker Karius; Hermann Behling (Global Change Biology, 2020)
The identification and quantification of natural carbon (C) sinks is critical to global climate change mitigation efforts. Tropical coastal wetlands are considered important in this context, yet knowledge of their dynamics and quantitative data are still scarce. In order to quantify the C accumulation rate and understand how it is influenced by land use and climate change, a palaeoecological study was conducted in the mangrove‐fringed Segara Anakan Lagoon (SAL) in Java, Indonesia. A sediment core was age‐dated and analyzed for its pollen and spore, elemental and biogeochemical compositions. The results indicate that environmental dynamics in the SAL and its C accumulation over the past 400 years were controlled mainly by climate oscillations and anthropogenic activities. The interaction of these two factors changed the lagoon's sediment supply and salinity, which consequently altered the organic matter composition and deposition in the lagoon. Four phases with varying climates were identified. While autochthonous mangrove C was a significant contributor to carbon accumulation in SAL sediments throughout all four phases, varying admixtures of terrestrial C from the hinterland also contributed, with natural mixed forest C predominating in the early phases and agriculture soil C predominating in the later phases. In this context, climate‐related precipitation changes are an overarching control, as surface water transport through rivers serves as the “delivery agent” for the outcomes of the anthropogenic impact in the catchment area into the lagoon. Amongst mangrove‐dominated ecosystems globally, the SAL is one of the most effective C sinks due to high mangrove carbon input in combination with a high allochthonous carbon input from anthropogenically enhanced sediment from the hinterland and increased preservation. Given the substantial C sequestration capacity of the SAL and other mangrove‐fringed coastal lagoons, conservation and restoration of these ecosystems is vitally important for climate change mitigation.

First palaeoecological evidence of buffalo husbandry and rice cultivation in the Kerinci Seblat National Park in Sumatra, Indonesia - Christina A. Setyaningsih; Hermann Behling; Asmadi Saad; Lyudmila Shumilovskikh; Supiandi Sabiham; Siria Biagioni (Vegetation History and Archaeobotany, 2019)

Response of Mangroves to Late Holocene Sea-Level Change: Palaeoecological Evidence from Sumatra, Indonesia - Christina Ani Setyaningsih; Siria Biagioni; Asmadi Saad; Kaoru Kashima; Supiandi Sabiham; Hermann Behling (Wetlands, 2019)

Human-made fires and forest clearance as evidence for late Holocene landscape domestication in the Orinoco Llanos (Venezuela) - Alejandra Leal; Rafael Gassón; Hermann Behling; Fernando Sánchez (Vegetation History and Archaeobotany, 2019)

Shifts of the Brazil-Falklands/Malvinas Confluence in the western South Atlantic during the latest Pleistocene–Holocene inferred from dinoflagellate cysts - Fang Gu; Cristiano M. Chiessi; Karin A. F. Zonneveld; Hermann Behling (Palynology, 2019)

Late Holocene vegetation, climate, human and fire history of the forest-steppe-ecosystem inferred from core G2-A in the ‘Altai Tavan Bogd’ conservation area in Mongolia - Julia Unkelbach; Choimaa Dulamsuren; Gaadan Punsalpaamuu; Davaadorj Saindovdon; Hermann Behling (Vegetation History and Archaeobotany, 2018)

Mid-Holocene vegetation dynamics with an early expansion of Mauritia flexuosa palm trees inferred from the Serra do Tepequém in the savannas of Roraima State in Amazonia, northwestern Brazil - Paula A. Rodríguez-Zorro; Marcondes Lima da Costa; Hermann Behling (Vegetation History and Archaeobotany, 2017)

High-resolution multi-proxy reconstruction of environmental changes in coastal waters of the Java Sea, Indonesia, during the late Holocene - Anastasia Poliakova; Karin A.F. Zonneveld; Lucia S. Herbeck; Tim C. Jennerjahn; Haryadi Permana; Cornelia Kwiatkowski; Hermann Behling (Palynology, 2017)

Vegetation and pollen along a 200-km transect in Khyber Pakhtunkhwa Province, northwestern Pakistan - Farooq Jan; Lisa Schüler; Hermann Behling (Palynology, 2016)

Differentiating vegetation types from eastern South American ecosystems based on modern and subfossil pollen samples: evaluating modern analogues - Jackson Martins Rodrigues; Hermann Behling; Thomas Giesecke (Vegetation History and Archaeobotany, 2016)

Unravelling the past 1,000 years of history of human–climate–landscape interactions at the Lindu plain, Sulawesi, Indonesia - Siria Biagioni; Torsten Haberzettl; Liang-Chi Wang; Guillaume St-Onge; Hermann Behling (Vegetation History and Archaeobotany, 2016)

Mid- and late Holocene vegetation and environmental dynamics in the Llanganates National Park, Anteojos Valley, central Ecuadorian Andes - Andrea Villota; Susana León-Yánez; Hermann Behling (Palynology, 2015)

Possible linkages of palaeofires in southeast Amazonia to a changing climate since the Last Glacial Maximum - Barbara Hermanowski; Marcondes Lima Da Costa; Hermann Behling (Vegetation History and Archaeobotany, 2015)

New insights into vegetation, climate and fire history of southern Brazil revealed by a 40,000 year environmental record from the State Park Serra do Tabuleiro - Vivian Jeske-Pieruschka; Valerio D. Pillar; Marcelo A. T. De Oliveira; Hermann Behling (Vegetation History and Archaeobotany, 2013)

Transport of airborne Picea schrenkiana pollen on the northern slope of Tianshan Mountains (Xinjiang, China) and its implication for paleoenvironmental reconstruction - Yanfang Pan; Shun Yan; Hermann Behling; Guijin Mu (Aerobiologia, 2013)

An integrated approach to relate Holocene climatic, hydrological, morphological and vegetation changes in the southeastern Amazon region - José Tasso Felix Guimarães; Marcelo Cancela Lisboa Cohen; Marlon Carlos França; Igor Charles Castor Alves; Clarisse Beltrão Smith; Luiz Carlos Ruiz Pessenda; Hermann Behling (Vegetation History and Archaeobotany, 2013)

Increased precipitation during the Little Ice Age in northern Taiwan inferred from diatoms and geochemistry in a sediment core from a subalpine lake - Liang-Chi Wang; Hermann Behling; Teh-Quei Lee; Hong-Chun Li; Chih-An Huh; Liang-Jian Shiau; Su-Hwa Chen; Jiunn-Tzong Wu (Journal of Paleolimnology, 2013)

A Holocene environmental record reflecting vegetation, climate, and fire variability at the Páramo of Quimsacocha, southwestern Ecuadorian Andes - Nele Jantz; Hermann Behling (Vegetation History and Archaeobotany, 2012)

Human–environment interactions in mountain rainforests: archaeobotanical evidence from central Sulawesi, Indonesia - Wiebke Kirleis; Valério D. Pillar; Hermann Behling (Vegetation History and Archaeobotany, 2011)

Poaceae pollen grain size as a tool to distinguish past grasslands in South America: a new methodological approach - Lisa Schüler; Hermann Behling (Vegetation History and Archaeobotany, 2011)

Characteristics of Poaceae pollen grains as a tool to assess palaeoecological grassland dynamics in South America - Lisa Schüler; Hermann Behling (Vegetation History and Archaeobotany, 2011)

Late Holocene vegetation, fire, climate and upper forest line dynamics in the Podocarpus National Park, southeastern Ecuador - Fernando Rodríguez; Hermann Behling (Vegetation History and Archaeobotany, 2011)

Holocene environmental dynamics of south-eastern Brazil recorded in laminated sediments of Lago Aleixo - Dirk Enters; Hermann Behling; Christoph Mayr; Lydie Dupont; Bernd Zolitschka (Journal of Paleolimnology, 2010)

Two‐step vegetation response to enhanced precipitation in Northeast Brazil during Heinrich event 1 - LYDIE M. DUPONT; FRANK SCHLÜTZ; CAROL TEBOH EWAH; TIM C. JENNERJAHN; ANDRÉ PAUL; HERMANN BEHLING (Global Change Biology, 2010)
High resolution palynological and geochemical data of sediment core GeoB 3910‐2 (located offshore Northeast Brazil) spanning the period between 19 600 and 14 500 calibrated year bp (19.6–14.5 ka) show a land‐cover change in the catchment area of local rivers in two steps related to changes in precipitation associated with Heinrich Event 1 (H1 stadial). At the end of the last glacial maximum, the landscape in semi‐arid Northeast Brazil was dominated by a very dry type of caatinga vegetation, mainly composed of grasslands with some herbs and shrubs. After 18 ka, considerably more humid conditions are suggested by changes in the vegetation and by C org and C/N data indicative of fluvial erosion. The caatinga became wetter and along lakes and rivers, sedges and gallery forest expanded. The most humid period was recorded between 16.5 and 15 ka, when humid gallery (and floodplain) forest and even small patches of mountainous Atlantic rain forest occurred together with dry forest, the latter being considered as a rather lush type of caatinga vegetation. During this humid phase erosion decreased as less lithogenic material and more organic terrestrial material were deposited on the continental slope of northern Brazil. After 15 ka arid conditions returned. During the humid second phase of the H1 stadial, a rich variety of landscapes existed in Northeast Brazil and during the drier periods small pockets of forest could probably survive in favorable spots, which would have increased the resilience of the forest to climate change.

Introduction: Tropical palaeoecology and global change - SIMON G. HABERLE; HERMANN BEHLING; LYDIE DUPONT; WIEBKE KIRLEIS (Global Change Biology, 2010)

Late‐glacial and Holocene vegetation, climate and fire dynamics in the Serra dos Órgãos, Rio de Janeiro State, southeastern Brazil - HERMANN BEHLING; HUGH DEFOREST SAFFORD (Global Change Biology, 2010)
We present a high‐resolution pollen and charcoal record of a 218 cm long sediment core from the Serra dos Órgãos, a subrange of the coastal Serra do Mar, located at 2130 m altitude in campos de altitude (high elevation grass‐ and shrubland) vegetation near Rio de Janeiro in southeastern Brazil to reconstruct past vegetation, climate and fire dynamics. Based on seven AMS 14 C ages, the record represents at least the last 10 450 14 C yr bp (12 380 cal years bp ), The uppermost region was naturally covered by campos de altitude throughout the recorded period. Diverse montane Atlantic rain forest (ARF) occurred close to the studied peat bog at the end of the Late‐glacial period. There is evidence of small Araucaria angustifolia populations in the study area as late as the early Holocene, after which point the species apparently became locally extinct. Between 10 380 and 10 170 14 C yr bp (12 310–11 810 cal yr bp ), the extent of campos de altitude was markedly reduced as montane ARF shifted rapidly upward to higher elevations, reflecting a very wet and warm period (temperatures similar to or warmer than present day) at the end of the Younger Dryas (YD) chronozone. This is in opposition to the broadly documented YD cooling in the northern Hemisphere. Reduced cross‐equatorial heat transport and movement of the Intertropical Convergence Zone over northeastern Brazil may explain the YD warming. Markedly extended campos de altitude vegetation indicates dry climatic conditions until about 4910 14 C yr bp (5640 cal yr bp ). Later, wetter conditions are indicated by reduced high elevation grassland and the extension of ARF into higher elevation. Fire frequency was high during the early Holocene but decreased markedly after about 7020 14 C yr bp (7850 cal yr bp ).

High-resolution studies on vegetation succession, hydrological variations, anthropogenic impact and genesis of a subrecent lake in southern Ecuador - Corinna Brunschön; Torsten Haberzettl; Hermann Behling (Vegetation History and Archaeobotany, 2010)

Late Holocene environmental change and human impact inferred from three soil monoliths and the Laguna Zurita multi-proxi record in the southeastern Ecuadorian Andes - Holger Niemann; Hermann Behling (Vegetation History and Archaeobotany, 2010)

Impact of sea-level and climatic changes on the Amazon coastal wetlands during the late Holocene - Marcelo Cancela Lisboa Cohen; Hermann Behling; Ruben José Lara; Clarisse Beltrão Smith; Hellen Rosy Soares Matos; Vincent Vedel (Vegetation History and Archaeobotany, 2009)

Holocene mangrove and coastal environmental changes in the western Ganga–Brahmaputra Delta, India - Arghya K. Hait; Hermann Behling (Vegetation History and Archaeobotany, 2009)

Late Quaternary vegetation, climate and fire dynamics inferred from the El Tiro record in the southeastern Ecuadorian Andes - Holger Niemann; Hermann Behling (Journal of Quaternary Science, 2008)
In order to study the stability and dynamics of mountain rainforest and paramo ecosystems, including the biodiversity of these ecosystems, the Holocene and late Pleistocene climate and fire variability, and human impact in the southeastern Ecuadorian Andes, we present a high‐resolution pollen record from El Tiro Pass (2810 m elevation), Podocarpus National Park. Palaeoenvironmental changes, investigated by pollen, spores and charcoal analysis, inferred from a 127 cm long core spanning the last ca. 21 000 cal. yr BP, indicate that grass‐paramo was the main vegetation type at the El Tiro Pass during the late Pleistocene period. The grass‐paramo was rich in Poaceae, Plantago rigida and Plantago australis , reflecting cold and moist climatic conditions. During the early Holocene, from 11 200 to 8900 cal. yr BP, subparamo and upper mountain rainforest vegetation expanded slightly, indicating a slow warming of climatic conditions during this period. From 8900 to 3300 cal. yr BP an upper mountain rainforest developed at the study site, indicated by an increase in Hedyosmun , Podocarpaceae, Myrsine and Ilex . This suggests a warmer climate than the present day at this elevation. The modern subparamo vegetation became established since 3300 cal. yr BP at El Tiro Pass. Fires, probably anthropogenic origin, were very rare during the late Pleistocene but became frequent after 8000 cal. yr BP. Copyright © 2007 John Wiley & Sons, Ltd.

A thankful tribute to Hans-Jürgen Beug on the occasion of his 75th birthday - Susanne Jahns; Lydie M. Dupont; Hermann Behling; Felix Bittmann; Frank Schlütz (Vegetation History and Archaeobotany, 2006)

Variability in glacial and Holocene marine pollen records offshore from west southern Africa - Lydie M. Dupont; Hermann Behling; Susanne Jahns; Fabienne Marret; Jung-Hyun Kim (Vegetation History and Archaeobotany, 2006)

Late Quaternary vegetation, fire and climate dynamics of Serra do Araçatuba in the Atlantic coastal mountains of Paraná State, southern Brazil - Hermann Behling (Vegetation History and Archaeobotany, 2006)

Holocene mangrove dynamics and sea-level changes in northern Brazil, inferences from the Taperebal core in northeastern Pará State - Vincent Vedel; Hermann Behling; Marcelo Cohen; Ruben Lara (Vegetation History and Archaeobotany, 2006)

A Model of Holocene Mangrove Development and Relative Sea-level Changes on the Bragança Peninsula (Northern Brazil) - Marcelo C. L. Cohen; Pedro W. M. Souza Filho; Rubén J. Lara; Hermann Behling; Rodolfo J. Angulo (Wetlands Ecology and Management, 2005)

Impacts of rapid sea‐level rise on mangrove deposit erosion: application of taraxerol and Rhizophora records - Jung‐Hyun Kim; Lydie Dupont; Hermann Behling; Gerard J. M. Versteegh (Journal of Quaternary Science, 2005)
We investigated a well‐dated marine sediment core from the tropical SE Atlantic covering the last 25 kyr, applying taraxerol and Rhizophora pollen as organic geochemical and palynological proxies for mangrove, respectively. Taraxerol records are positively correlated with Rhizophora pollen records, showing an enhanced supply of mangrove materials into deep‐sea environments during the last deglaciation (Termination I). Sedimentation rates peaked during Meltwater Pulses 1A and 1B, which were associated with the maxima of taraxerol and Rhizophora pollen. This study supports the view that mangrove input was dominantly controlled by erosion of mangrove‐rich shelf sediments during the transgressions. Whether reworked materials were penecontemporaneous or from much older deposits formed during previous sea‐level cycles is discussed. Copyright © 2005 John Wiley & Sons, Ltd.

Colombian vegetation at the Last Glacial Maximum: a comparison of model‐ and pollen‐based biome reconstructions - Robert Marchant; Arnoud Boom; Hermann Behling; Henry Hooghiemstra; Bert Melief; Bas Van Geel; Thomas Van der Hammen; Michael Wille (Journal of Quaternary Science, 2004)
Colombian vegetation, at the ecological level of the biome, is reconstructed at the Last Glacial Maximum (LGM) using two methods. A reconstruction of modern biomes shows that, for the majority of the sites, the pollen data accurately reflect the potential vegetation, even though much of the original vegetation has been transformed by agricultural practices. At 18 000 14 C yr BP a generally cool and dry environment is reflected in biome assignments of cold mixed forests, cool evergreen forests and cool grassland/shrub, the latter extending to lower altitudes than presently recorded. Differential responses of the vegetation to climatic shifts are related to changes in moisture sources and the importance of edaphic control on the vegetation. Secondly, biomes at the LGM are also investigated by applying a vegetation model (BIOME‐3) set to operate at CO 2 levels of 200 ppmV and with climatic data from 12 meteorological stations that encompass a range of environments within Colombia. At lower altitudes it is apparent that moisture is the dominant control on driving vegetation change whereas temperature becomes more important at higher altitudes. The combined reconstruction of biome‐scale vegetation dynamics in Colombia allows an understanding of the environmental controls on these to be developed that demonstrates the need to invoke different factors to explain the vegetation change rather than a uniform reduction in temperature or moisture. Copyright © 2004 John Wiley & Sons, Ltd.

Mangrove ecosystem dynamics and elemental cycling at Twin Cays, Belize, during the Holocene - Matthew J. Wooller; Hermann Behling; Barbara J. Smallwood; Marilyn Fogel (Journal of Quaternary Science, 2004)
Existing at the transition between the terrestrial environment and hydrosphere, mangroves are sensitive to environmental change (e.g. sea‐level rise). We present pollen and stable isotope data from a core (TCC1) of continuous (10 m) mangrove peat from Twin Cays, ∼12 km off of the coast of Belize, Central America. Radiocarbon dates on fragments of mangrove leaves preserved in TCC1 show that the core provides an 8600 14 C year record of mangrove ecosystem changes. Variation in the stable carbon and nitrogen isotope composition (δ 13 C = ∼−30 to −25‰; δ 15 N = ∼−6 to 2‰) of mangrove leaves imply that the stand structure and nutrient status of the mangroves at the site have changed during the Holocene. Pollen data from the same core show that the floral composition of the site has changed at points during the Holocene, most notably a brief (∼240 years) switch at ∼3860 14 C yr BP to dominance by a species of Myrsine (not currently present at the site). Our results are consistent with significant environmental changes (either marked disturbance from hurricanes or fluctuations in sea‐level) through the Holocene. Copyright © 2004 John Wiley & Sons, Ltd.

Late Holocene mangrove dynamics of Maraj Island in Amazonia, northern Brazil - Hermann Behling; MarceloC.L. Cohen; RubnJ. Lara (Vegetation History and Archaeobotany, 2004)

Late glacial and Holocene vegetation, climate and fire history inferred from Lagoa Nova in the southeastern Brazilian lowland - Hermann Behling (Vegetation History and Archaeobotany, 2003)

Pollen‐based biome reconstructions for Colombia at 3000, 6000, 9000, 12 000, 15 000 and 18 000 14 C yr ago: Late Quaternary tropical vegetation dynamics - Robert Marchant; Hermann Behling; Juan‐Carlos Berrio; Antoine Cleef; Joost Duivenvoorden; Henry Hooghiemstra; Peter Kuhry; Bert Melief; Elisabeth Schreve‐Brinkman; Bas Van Geel; Thomas Van der Hammen; Guido Van Reenen; et al. (Journal of Quaternary Science, 2002)
Colombian biomes are reconstructed at 45 sites from the modern period extending to the Last Glacial Maximum (LGM). The basis for our reconstruction is pollen data assigned to plant functional types and biomes at six 3000‐yr intervals. A reconstruction of modern biomes is used to check the treatment of the modern pollen data set against a map of potential vegetation. This allows the biomes reconstructed at past periods to be assessed relative to the modern situation. This process also provides a check on the a priori assignment of pollen taxa to plant functional types and biomes. For the majority of the sites, the pollen data accurately reflect the potential vegetation, even though much of the original vegetation has been transformed by agricultural practices. At 18 000 14 C yr BP, a generally cool and dry environment is reflected in biome, assignments of cold mixed forests, cool evergreen forests and cool grassland–shrub; the latter extending to lower altitudes than presently recorded. This signal is strongly recorded at 15 000 and 12 000 14 C yr BP, the vegetation at these times also reflecting a relatively cool and dry environment. At 9000 14 C yr BP there is a shift to biomes thought to result from slightly cooler environmental conditions. This trend is reversed by 6000 14 C yr BP; most sites, within a range of different environmental settings, recording a shift to more xeric biome types. There is an expansion of steppe and cool mixed‐forest biomes, replacing tropical dry forest and cool grassland–shrub biomes, respectively. These changes in biome assignments from the modern situation can be interpreted as a biotic response to mid‐Holocene climatic aridity. At 3000 14 C yr BP the shift is mainly to biomes characteristic of slightly more mesic environmental conditions. There are a number of sites that do not change biome assignment relative to the modern reconstruction, although the affinities that these sites have to a specific biome do change. These ‘anomalies’ are interpreted on a site‐by‐site basis. Spatially constant, but differential response of the vegetation to climatic shifts are related to changes in moisture sources and the importance of edaphic controls on the vegetation. The Late Quaternary reconstruction of large‐scale vegetation dynamics in Colombia allows an understanding of the environmental controls on these to be developed. In particular, shifts in the character of the main climatic systems that influence Colombian vegetation are described. Copyright © 2002 John Wiley & Sons, Ltd.

Holocene Amazon rainforest-savanna dynamics and climatic implications: high-resolution pollen record from Laguna Loma Linda in eastern Colombia - Hermann Behling; Henry Hooghiemstra (Journal of Quaternary Science, 2000)

Palaeoecological studies at the Mesolithic site at Bedburg-Knigshov near Cologne, Germany - Hermann Behling; Martin Street (Vegetation History and Archaeobotany, 1999)

Environmental history of the Colombian savannas of the Llanos Orientales since the Last Glacial Maximum from lake records El Pinal and Carimagua - Hermann Behling; Henry Hooghiemstra (Journal of Paleolimnology, 1999)

Late Quaternary vegetational and climatic change in the Popayán region, southern Colombian Andes - Hermann Behling; Alvaro José Negret; Henry Hooghiemstra (Journal of Quaternary Science, 1998)